STUDIES ONANTICANDIDAL ACTIVITY OF THE ACTINOMYCETES ISOLATED FROM COIMBATORE REGION OF TAMILNADU - C. SWEETLINE; R. USHA; M.PALANISWAMY (International Journal of Pharma and Bio Sciences, 2014)
A novel actinomycetes strain designated KMA15, producing anticandidal substances was isolated from different locations in Coimbatore has been studied. Morphological and biochemical studies indicated that strain KMA15 belonged to the genus Streptomyces. A total of 35 actinomycetes were subjected to agar disc method against Candida albicans. It was observed that 12 isolates were active against Candida albicans. The anticandidal substances were extracted by solvent extraction method with ethanol from isolate inoculated in yeast malt extract broth fermented for 7 days 280C. Fungicidal activity was determined by observing clear zone, the actinomycetes strain KMA15 possessed great fungicidal activity for Candida albicans by showing the 22mm of zone of inhibition.Minimum inhibitory concentration of the solvent extract was determined as 1.562 mg/ml against Candida albicans. The antifungal substance active against the Candida albicans were purified using column chromatography. The nature and further biological activity of the active principle are under investigation